2024
DOI: 10.1167/tvst.13.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of 0.01% and 0.05% Atropine Eyedrops on Ocular Surface in Young Adults

Yifan Luo,
Ziang Yin,
Jiali Zhang
et al.

Abstract: Purpose To evaluate the effect of low-concentration (0.01% and 0.05%) atropine eyedrops on ocular surface characteristics in young adults. Methods Twenty-six myopic students aged 18 to 30 years were randomly assigned to receive either 0.01% or 0.05% atropine once nightly for 14 days, followed by cessation, with a ≥14-day interval between each administration. Assessments were conducted one, two, seven, and 14 days after using atropine with corresponding timepoints after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…A retrospective analysis conducted in Germany by Kaymak et al [ 38 ] revealed that nearly 17.0% of children treated with 0.01% atropine reported side effects such as burning eyes following drop instillation, pupil dilatation, photophobia or eye redness. Another study evaluating the impact of 0.01% and 0.05% atropine eye drops on the ocular surface in young myopic adults concluded that 0.05% atropine has a significant yet temporary effect on the tear film and 0.01% atropine has minimal impact on the ocular surface [ 13 ]. In a study by Medghalchi et al [ 39 ], four patients (16%) in the 0.1% atropine group experienced headaches compared to none in 0.01% group ( p = 0.032), while 11 patients (44%) in the 0.1% atropine group had photophobia compared to four patients (20%) in the 0.01% atropine group ( p = 0.001); additionally, 11 patients (44%) in the 0.1% atropine group experienced blurred vision, while none in the 0.01% atropine group had this side effect ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective analysis conducted in Germany by Kaymak et al [ 38 ] revealed that nearly 17.0% of children treated with 0.01% atropine reported side effects such as burning eyes following drop instillation, pupil dilatation, photophobia or eye redness. Another study evaluating the impact of 0.01% and 0.05% atropine eye drops on the ocular surface in young myopic adults concluded that 0.05% atropine has a significant yet temporary effect on the tear film and 0.01% atropine has minimal impact on the ocular surface [ 13 ]. In a study by Medghalchi et al [ 39 ], four patients (16%) in the 0.1% atropine group experienced headaches compared to none in 0.01% group ( p = 0.032), while 11 patients (44%) in the 0.1% atropine group had photophobia compared to four patients (20%) in the 0.01% atropine group ( p = 0.001); additionally, 11 patients (44%) in the 0.1% atropine group experienced blurred vision, while none in the 0.01% atropine group had this side effect ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Among the strategies available for managing myopia progression, atropine eye drops are widely regarded as one of the most effective interventions, with numerous studies demonstrating their ability to effectively and safely manage myopia progression in children, both those with premyopia and those already myopic [ 7 , 8 , 9 , 10 , 11 ]. However, it is important to note that the efficacy of atropine is concentration-dependent, with higher concentrations associated with increased risk of adverse events and rebound effects [ 11 , 12 , 13 ]. Post cessation of atropine eye drops, myopia tends to progress at a faster rate compared to its progression during treatment with atropine eye drops [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%